Composite phase change material as well as preparation method and application thereof
By using composite phase change materials combined with silicon dioxide shell and -Si-OLi modification group in lithium batteries, the problems of poor thermal conductivity and safety hazards are solved, and better battery performance and temperature are achieved control.
Patent Information
- Application Number
- CN202411270566.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
Existing phase change materials have poor thermal conductivity in lithium batteries, which affects battery performance, and have safety hazards and battery material compatibility problems.
The organic phase change material is used to combine with the silica shell and the -Si-OLi modified group, and microcapsules are formed through in-situ polymerization reaction, which are dispersed in the electrolyte to improve thermal conductivity and internal temperature uniformity of the battery.
It improves the thermal conductivity and electrical properties of lithium-ion batteries, avoids poor compatibility and safety hazards of battery materials, extends battery life and reduces temperature-related side reactions.
Smart Images

Figure CN119119967A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of phase change materials, and specifically relates to a composite phase change material and a preparation method and application thereof. Background Art
[0002] In recent years, the new energy vehicle industry has developed rapidly. Lithium-ion batteries have high energy density and wide application range, making them the first choice for new energy vehicles. The performance of lithium-ion batteries is also affected by various factors, among which temperature is the key factor affecting battery performance. When the temperature rises, the self-discharge rate of lithium batteries increases, resulting in capacity loss and reduced calendar life. High temperature will also accelerate the aging process of the battery and shorten the battery life. In addition, high temperature environment may also trigger certain chemical reactions inside the battery, causing battery safety problems.
[0003] During the use of batteries, a lot of heat is generated. Due to the dense stacking of battery cells in the battery pack, it is relatively more difficult to dissipate heat in the middle area to a certain extent, which aggravates the temperature inconsistency between battery cells. Therefore, it is very necessary to manage the battery thermally so that the battery can work stably within an appropriate range. The current thermal management system includes air cooling, liquid cooling and phase change material cooling system. Phase change materials can absorb a lot of heat during the phase change process. In the phase change material cooling system, the battery is usually immersed in the phase change material. Full contact can enhance heat exchange and maintain a small temperature change. Compared with liquid and air cooling systems, the phase change material cooling system has a simple structure, low energy consumption, and is suitable for a variety of working conditions.
[0004] For example, the prior art discloses a solution of directly compounding phase change materials between the two layers of aluminum shells of lithium batteries, but this may corrode the aluminum shells during long-term use, causing safety risks. The prior art also discloses a solution of dispersing phase change materials in microporous aluminum nitride ceramic spheres and then encapsulating the formed microcapsules in the lithium-ion battery shell, but this will result in low thermal conductivity, and when the temperature is high, the phase change material may leak from the micropores, affecting the battery performance; in addition, there is also a technology of coating phase change material microcapsules on the positive electrode current collector, but the pole piece production process requires a rolling process, which is bound to affect the performance of the microcapsules, and the microcapsules will also affect the electronic conductivity of the pole piece itself. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present application is to overcome the defects of the phase change materials in the prior art in lithium battery applications, such as poor thermal conductivity and the effect on the electrical performance of the battery, thereby providing a composite phase change material and its preparation method and application.
[0006] To this end, this application provides the following technical solutions:
[0007] According to one aspect of the present application, a composite phase change material is provided, comprising:
[0008] Organic phase change materials;
[0009] A shell layer is coated on the surface of the phase change material; wherein the shell layer includes silicon dioxide and -Si-OLi modification groups.
[0010] In some optional embodiments, the Dv50 of the composite phase change material is 1-5 μm;
[0011] And / or, based on the total mass of the composite phase change material, the organic phase change material accounts for 55-85%.
[0012] In some optional embodiments, the phase change temperature of the organic phase change material is 30°C-45°C;
[0013] Optionally, the organic phase change material includes one or a mixture of PEG100, octadecane, paraffin, hexadecanol, glyceryl distearate, and ethylene glycol monostearate.
[0014] In the present application, if a single organic phase change material has a high phase change temperature, it can be used in combination with an organic phase change material with a lower phase change temperature.
[0015] According to another aspect of the present application, a method for preparing the above-mentioned composite phase change material is provided, comprising the following steps:
[0016] S1, heating the organic phase change material (to increase its fluidity), mixing it with a surfactant and water to form an O / W emulsion;
[0017] S2, adding a silane precursor to the above O / W emulsion, adjusting the pH, and performing an in-situ polymerization reaction to obtain phase change microcapsules;
[0018] S3, dispersing the phase change microcapsules in a non-protonic solvent, and reacting with alkyl lithium to obtain the composite phase change material.
[0019] In some optional embodiments, the mass ratio of the organic phase change material, the surfactant, and the silane precursor is 10-15:2:10-15.
[0020] In some optional embodiments, in step S1, the mixing stirring speed is 1000-6000 rpm; the size of the obtained oil droplets is 1-5 μm;
[0021] And / or, the surfactant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyl betaine sulfate, polyoxyethylene sorbitan monolaurate, hexadecyl trimethyl ammonium bromide, and dodecyl betaine.
[0022] In some optional embodiments, in step S2, the temperature of the in-situ polymerization reaction is 60-80° C., and the reaction time is 6-24 h;
[0023] And / or, the in-situ polymerization reaction is carried out under stirring at 500-1000 rpm;
[0024] and / or, adjusting the pH to 4.5-6.5;
[0025] And / or, the silane precursor includes at least one of tetraethyl orthosilicate, tetramethylsilane, tetrapropylsilane, triethoxysilane, trimethoxysilane, disubstituted silane Si(OR)2X2 or monosubstituted silane Si(OR)3X (R is alkyl or aryl, X is H, alkyl, etc.).
[0026] In some optional embodiments, in step S3, the reaction temperature is -70°C to 0°C;
[0027] And / or, the amount of the alkyl lithium is 1-3% of the mass of the microcapsule;
[0028] And / or, the reaction is carried out under a protective atmosphere;
[0029] And / or, the alkyl lithium includes at least one of methyl lithium, ethyl lithium and n-butyl lithium, and the amount used is 1-3% of the mass of the microcapsule;
[0030] And / or, the aprotic solvent includes at least one of tetrahydrofuran, dimethoxyethane, diethyl ether, acetonitrile, propionitrile and dimethyl sulfoxide.
[0031] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned composite phase change material or the composite phase change material prepared by the above-mentioned preparation method;
[0032] Optionally, the composite phase change material is added to the electrolyte of a lithium-ion battery;
[0033] Further optionally, the addition amount of the composite phase change material satisfies: M add =T max ·M battery ·C battery / L / ω, where T max The maximum temperature rise allowed by the battery, in degrees Celsius, C battery The specific heat capacity of the battery, in J / g·℃, M battery is the mass of the battery in g, L is the latent heat of the phase change material in J / g, and ω is the mass fraction of the organic phase change material in the composite phase change material.
[0034] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned lithium-ion battery.
[0035] In the present application, the Dv50 of the composite phase change material can be tested by methods and equipment known in the art, for example, by using a laser particle size analyzer.
[0036] In the present application, the mass ratio of the organic phase change material in the composite phase change material can be tested by methods and equipment known in the art, for example, by using a thermogravimetric analyzer.
[0037] In the present application, the size of the oil droplets can be tested using methods and equipment known in the art, for example, using an optical microscope for testing.
[0038] Specifically, the preparation method of the composite phase change material provided in the present application includes:
[0039] (1) heating the organic phase change material to a suitable temperature to increase its fluidity, adding a surfactant and deionized water, stirring and emulsifying it to disperse it into oily small droplets to form an O / W emulsion;
[0040] (2) adding the O / W emulsion obtained in (1) into a three-necked flask, adjusting the rotation speed and temperature to heat in a water bath, adding a silane precursor thereto, and adding a hydrochloric acid solution or the like to adjust the pH, so that an in-situ polymerization reaction occurs; after reacting for 12 hours, washing the obtained microcapsules with distilled water until they are neutral, and drying them in a forced air oven at 80° C. (for example, drying can be performed for any time until the moisture content of the microcapsules is less than 200 ppm), to obtain phase change microcapsules;
[0041] (3) Dispersing the above microcapsules in a dry aprotic solvent and maintaining an oxygen-free and water-free environment and cooling conditions, and introducing an inert gas atmosphere, adding alkyl lithium accounting for 1-3% of the mass ratio of the microcapsules, slowly stirring, after the reaction is complete (about 1-4 hours, such as methyl lithium 2-4 hours, ethyl lithium 1-2 hours, n-butyl lithium 1 hour), filtering and washing with acetone, and vacuum drying to obtain the desired composite phase change material.
[0042] In the present application, the heating temperature in step (1) is adjusted by those skilled in the art according to the selection of the organic phase change material and the phase change temperature, as long as the purpose of increasing its fluidity can be achieved.
[0043] In the present application, the lithium-ion batteries provided are not particularly limited and are conventional in the field. Typically, but not limitedly, they can be lithium-ion batteries assembled from any positive electrode active material such as lithium iron (manganese) phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, and any negative electrode active material such as graphite, silicon-based negative electrode material, lithium titanate, etc.
[0044] In the present application, the electrical equipment using the above-mentioned lithium-ion battery is not particularly limited. Typically, the electrical equipment includes, but is not limited to, mobile phones, laptops, tablet computers, pen-input computers, portable fax machines, portable copiers, portable printers, transceivers, video recorders, cameras, televisions, radios, portable recorders, portable CD players, mini-discs, e-book players, electronic notepads, wearable devices (such as smart watches, smart bracelets, head-mounted stereo headphones, Bluetooth headphones), portable cleaners, calculators, memory cards, backup power supplies, cars, motorcycles, bicycles (such as power-assisted bicycles), lighting fixtures (such as flashlights), toys, game consoles, clocks, power tools, large household batteries, capacitors, etc.
[0045] The technical solution of this application has the following advantages:
[0046] The composite phase change material provided by the present application includes: an organic phase change material; a shell layer, coated on the surface of the phase change material; wherein the shell layer includes silicon dioxide and -Si-OLi modification groups. In the present application, the encapsulation of the organic phase change material by the shell layer (i.e., forming microcapsules) solves the problem of poor compatibility between the phase change material and the battery material; the use of inorganic silicon dioxide in the shell layer can avoid reaction with the electrolyte without affecting the inherent performance of the battery; the shell layer is modified with -Si-OLi groups, and when it is used in the electrolyte, it will be ionized to form -Si-O - The electrostatic repulsion between the microcapsules makes them dispersed evenly and also ensures the uniform temperature inside the battery. + It is also possible to increase the Li content in the electrolyte + concentration, reducing diffusion impedance and improving electrical performance.
[0047] The composite phase change material provided by the present application can make the particle size distribution of the microcapsules more uniform by limiting the particle size, thereby improving the dispersibility. The microcapsules with narrow particle size distribution are more easily dispersed in the electrolyte and reduce the agglomeration phenomenon. At the same time, by controlling the particle size, the potential safety hazards of the microcapsules in the battery can be reduced, such as avoiding problems such as internal short circuits caused by excessive particle size.
[0048] The composite phase change material provided by the present application can control the battery temperature at a lower level by limiting the phase change temperature of the organic phase change material, thereby further improving the electrical performance of the battery. This is because when the temperature rises above 30°C, the side reactions inside the lithium-ion battery increase, and the storage and cycle performance begin to decline.
[0049] The preparation method of the composite phase change material provided by the present application first prepares the phase change microcapsules, and generates a continuous SiO2 network structure shell on the surface of the organic phase change material during the reaction process, forming a uniform and dense protective layer; at the same time, during the formation of the shell, Si-OH groups will be left on the surface, because the first step of the hydrolysis of the silane precursor is to generate silanol groups, and then these groups will participate in the condensation reaction to form a Si-O-Si network structure. However, not all Si-OH groups will participate in the condensation reaction to form a solid silica network, so some unreacted Si-OH groups will usually remain on the surface of the shell. Then alkyl lithium is used for modification to form -Si-OLi groups. Compared with the prior art, this method is simple to operate and easy to control, and the resulting composite phase change material will not only not affect the electrical properties, but also reduce impedance and improve electrical properties.
[0050] The lithium-ion battery provided by the present application preferably adds the composite phase change material into the electrolyte to solve the problem of poor thermal conductivity. The inorganic shell (SiO2) can avoid reacting with the electrolyte and does not affect the inherent performance of the battery. At the same time, the Li ionized in the electrolyte + It is also possible to increase the Li content in the electrolyte + concentration, reducing diffusion impedance and improving electrical performance.
[0051] The lithium-ion battery provided in the present application, the amount of the composite phase change material added satisfies the formula: M add =T max ·M battery ·C battery / L / ω. By limiting the amount of addition, the present application can ensure that the composite phase change material can meet the heat dissipation requirements without affecting the electrical performance due to excessive addition. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0053] Figure 1 This application is + Diffusion coefficient test step. DETAILED DESCRIPTION
[0054] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0055] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0056] Example 1
[0057] This embodiment provides a composite phase change material, the specific composition of which includes:
[0058] Organic phase change materials;
[0059] The shell layer is coated on the surface of the phase change material; wherein the shell layer includes silicon dioxide and -Si-OLi modification groups; the operation steps and specific parameters of the preparation method are as follows:
[0060] (1) 15 g of paraffin was heated to 60° C., 2 g of sodium dodecylbenzene sulfonate and 100 g of deionized water were added, and the mixture was stirred and emulsified at 2000 rpm to disperse the mixture into oily droplets of 3 μm to form an O / W emulsion;
[0061] (2) The O / W emulsion obtained in (1) was added to a three-necked flask, stirred at 600 rpm, heated in a water bath at 70° C., 15 g of tetraethyl orthosilicate was added, and a hydrochloric acid solution was added to adjust the pH to 6 to allow an in-situ polymerization reaction to occur. After the reaction lasted for 12 h, the obtained phase change microcapsules were washed with distilled water until neutral, and dried in a forced air oven at 80° C. until the water content was below 200 ppm;
[0062] (3) The phase change microcapsules are dispersed in dry tetrahydrofuran to maintain an oxygen-free and water-free environment (-40°C), and a nitrogen atmosphere is introduced. 1% of n-butyl lithium is added to the microcapsules by mass, and the mixture is stirred slowly for 1 hour. The mixture is filtered and washed with acetone, and then vacuum dried to obtain the desired composite phase change material.
[0063] Example 2
[0064] This embodiment provides a composite phase change material, the specific composition of which includes:
[0065] Organic phase change materials;
[0066] The shell layer is coated on the surface of the phase change material; wherein the shell layer includes silicon dioxide and -Si-OLi modification groups; the operation steps and specific parameters of the preparation method are as follows:
[0067] (1) 10 g of paraffin was heated to 60° C., 2 g of sodium dodecylbenzene sulfonate and 100 g of deionized water were added, and the mixture was stirred and emulsified at 1000 rpm to disperse the mixture into oily droplets of 5 μm to form an O / W emulsion;
[0068] (2) The O / W emulsion obtained in (1) was added to a three-necked flask, stirred at 1000 rpm, heated in a water bath at 60° C., 10 g of tetraethyl orthosilicate was added, and a hydrochloric acid solution was added to adjust the pH to 6 to allow an in-situ polymerization reaction to occur. After the reaction lasted for 12 h, the obtained phase change microcapsules were washed with distilled water until neutral, and dried in a forced air oven at 80° C. until the water content was below 200 ppm;
[0069] (3) The phase change microcapsules are dispersed in dry tetrahydrofuran to maintain an oxygen-free and water-free environment (-70°C), and a nitrogen atmosphere is introduced. 1% of n-butyl lithium is added to the microcapsules by mass, and the mixture is stirred slowly for 1 hour. The mixture is filtered and washed with acetone, and then vacuum dried to obtain the desired composite phase change material.
[0070] Example 3
[0071] This embodiment provides a composite phase change material, the specific composition of which includes:
[0072] Organic phase change materials;
[0073] The shell layer is coated on the surface of the phase change material; wherein the shell layer includes silicon dioxide and -Si-OLi modification groups; the operation steps and specific parameters of the preparation method are as follows:
[0074] (1) 13 g of paraffin was heated to 60° C., 2 g of sodium dodecylbenzene sulfonate and 100 g of deionized water were added, and the mixture was stirred and emulsified at 6000 rpm to disperse the mixture into oily droplets of 1 μm to form an O / W emulsion;
[0075] (2) The O / W emulsion obtained in (1) was added to a three-necked flask, stirred at 500 rpm, heated in a water bath at 80° C., 13 g of tetraethyl orthosilicate was added thereto, and a hydrochloric acid solution was added to adjust the pH to 6 to allow an in-situ polymerization reaction to occur. After the reaction lasted for 12 h, the obtained phase change microcapsules were washed with distilled water until neutral, and dried in a forced air oven at 80° C. until the water content was below 200 ppm;
[0076] (3) The phase change microcapsules are dispersed in dry tetrahydrofuran to maintain an oxygen-free and water-free environment (0°C), and a nitrogen atmosphere is introduced. 1% of n-butyl lithium is added to the microcapsules by mass, and the mixture is stirred slowly for 1 hour. The mixture is filtered and washed with acetone, and then vacuum dried to obtain the desired composite phase change material.
[0077] Example 4
[0078] This embodiment provides a composite phase change material, the specific composition of which includes:
[0079] Organic phase change materials;
[0080] The shell layer is coated on the surface of the phase change material; wherein the shell layer includes silicon dioxide and -Si-OLi modification groups; the operation steps and specific parameters of the preparation method are as follows:
[0081] (1) 15 g of ethylene glycol monostearate was heated to 60° C., 2 g of sodium dodecyl sulfate and 100 g of deionized water were added, and the mixture was stirred and emulsified at 2000 rpm to disperse the mixture into oily droplets of 3 μm to form an O / W emulsion;
[0082] (2) adding the O / W emulsion obtained in (1) into a three-necked flask, stirring at 600 rpm, heating in a water bath at 70° C., adding 15 g of triethoxysilane, and adding hydrochloric acid solution to adjust the pH to 6, so that an in-situ polymerization reaction occurs. After reacting for 12 h, the obtained phase change microcapsules are washed with distilled water until neutral, and dried in a forced air oven at 80° C. until the water content is below 200 ppm;
[0083] (3) The phase change microcapsules are dispersed in dry diethyl ether to maintain an oxygen-free and water-free environment (-40°C), and a nitrogen atmosphere is introduced. Ethyl lithium accounting for 2% of the mass ratio of the microcapsules is added thereto, and stirred slowly. After 2 hours, the mixture is filtered and washed with acetone, and then vacuum dried to obtain the desired composite phase change material.
[0084] Comparative Example 1
[0085] This comparative example provides a composite phase change material, the specific composition of which includes:
[0086] Organic phase change materials;
[0087] The shell layer is coated on the surface of the phase change material; wherein the shell layer comprises silicon dioxide; the operation steps and specific parameters of the preparation method are as follows:
[0088] (1) 10 g of paraffin was heated to 60° C., 2 g of sodium dodecylbenzene sulfonate and 100 g of deionized water were added, and the mixture was stirred and emulsified at 1000 rpm to disperse the mixture into oily droplets of 5 μm to form an O / W emulsion;
[0089] (2) The O / W emulsion obtained in (1) was added to a three-necked flask, stirred at 1000 rpm, heated in a water bath at 60°C, 10 g of tetraethyl orthosilicate was added, and hydrochloric acid solution was added to adjust the pH to 6 to allow an in-situ polymerization reaction to occur. After reacting for 12 hours, the obtained phase change microcapsules were washed with distilled water until neutral, and dried in a forced air oven at 80°C until the water content was below 200 ppm, thereby obtaining the desired composite phase change material.
[0090] Comparative Example 2
[0091] This comparative example provides a soft-pack battery. Take the same soft-pack battery as in the following test example, wrap a thin layer of double-sided tape around the surface of the soft-pack battery, inject electrolyte into the soft-pack battery, and obtain the desired soft-pack battery after pre-charging.
[0092] Comparative Example 3
[0093] This comparative example provides a soft-pack battery. Take the same soft-pack battery as in the following test example, wrap a thin layer of double-sided tape around the surface of the soft-pack battery, evenly sprinkle 10g of the composite phase change material provided in Example 1 on the surface of the soft-pack battery, inject the electrolyte into the soft-pack battery, and obtain the desired soft-pack battery after pre-charging.
[0094] Test Case
[0095] The composite phase change materials prepared in each embodiment and comparative example were subjected to performance tests, and the specific test methods are as follows:
[0096] Take a 4Ah standard lithium iron phosphate / graphite soft-pack battery to be filled, inject the electrolyte (EC:DMC:EMC mass ratio of 1:1:1, 1 mol / L LiPF6) (including or not including composite phase change material) into the soft-pack battery, and obtain the required soft-pack battery after pre-charging.
[0097] Formed gram capacity: The formation temperature is 30±5℃, and the battery is formed using a blue battery. The battery to be formed is left to stand for 30 minutes, and a small current of 0.1C is used to charge the battery to a predetermined voltage of 3.65V under constant current and constant voltage. The battery is left to stand for 1 hour to allow the internal reaction of the battery to reach equilibrium, and a small current of 0.1C is used to discharge the battery under constant current to the termination voltage (2.5V), and the charge and discharge capacity is recorded.
[0098] 3C full charge temperature rise: The soft-pack battery is charged at a rate of 3C to 100% SOC. Taking lithium iron phosphate battery as an example, the voltage range is 2.5-3.65V. A thermocouple is placed at the same position on the battery surface to monitor the change of battery temperature from the initial to 100% SOC.
[0099] 3C full discharge temperature rise: Let the battery charged to 100% SOC stand for 30 minutes, and after it returns to room temperature, discharge it to 0% SOC at a rate of 3C. Taking lithium iron phosphate battery as an example, the voltage range is 2.5-3.65V. Place a thermocouple at the same position on the battery surface to monitor the change of battery temperature from 100% SOC to 0% SOC.
[0100] Li + Diffusion coefficient (PITT): refer to Figure 1 The specific steps are as follows: activate the battery at 0.1C for two cycles, let it stand for 30 minutes, discharge it to empty, let it stand for another 30 minutes, charge it to 50% SOC at 0.33C, let it stand for 30 minutes, charge it at constant voltage for 300 minutes, and test the lithium ion diffusion coefficient of lithium iron phosphate at 50% SOC.
[0101] The specific test results are shown in the table below:
[0102] Table 1
[0103]
[0104]
[0105] By comparing the blank example with Example 1-1 and Example 1-2, it can be seen that after adding the composite phase change material to the electrolyte, the gram capacity of the battery has not changed, which means that the composite phase change material provided by the present application will not affect the inherent ion and electron transmission performance of the battery. At the same time, with the increase in the amount of composite phase change material added, the temperature rise of the battery is gradually decreasing. It can be seen from Example 1-2 and Comparative Example 3 that when the composite phase change material is added to the electrolyte, its temperature control of the battery is significantly better than placing the composite phase change material outside the battery shell, indicating that the thermal conductivity of the composite phase change material inside the battery is better than that outside. At the same time, the ion diffusion coefficient of the battery has also been significantly improved.
[0106] The composite phase change material is made by coating the organic phase change material with a silica inorganic shell by a one-step in-situ polymerization method, and the surface group is modified with alkyl lithium. It is placed in the electrolyte of the battery to reduce the temperature rise and improve the high temperature performance of the battery. The results show that the thermal conductivity of the composite phase change material inside the battery is better than that outside. This can not only reduce the self-discharge rate of the battery and increase the calendar life, but also reduce the side reactions of the electrolyte and increase the cycle performance. At the same time, this method can also be used in combination with liquid or air cooling systems.
[0107] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A composite phase change material, characterized in that: include: Organic phase change materials; A shell layer is coated on the surface of the phase change material; wherein the shell layer includes silicon dioxide and -Si-OLi modification groups.
2. The composite phase change material according to claim 1, characterized in that: The Dv50 of the composite phase change material is 1-5 μm; And / or, based on the total mass of the composite phase change material, the organic phase change material accounts for 55-85%.
3. The composite phase change material according to claim 1 or 2, characterized in that: The organic phase change material includes one or a mixture of PEG100, octadecane, paraffin, hexadecanol, distearic acid glyceryl, and ethylene glycol monostearate; Optionally, the phase change temperature of the organic phase change material is between 30°C and 45°C.
4. A method for preparing the composite phase change material according to any one of claims 1 to 3, characterized in that: The steps include: S1, heating the organic phase change material, mixing it with a surfactant and water to form an O / W emulsion; S2, adding a silane precursor to the above O / W emulsion, adjusting the pH, and performing an in-situ polymerization reaction to obtain phase change microcapsules; S3, dispersing the phase change microcapsules in a non-protonic solvent, and reacting with alkyl lithium to obtain the composite phase change material.
5. The method for preparing the composite phase change material according to claim 4, characterized in that: The mass ratio of the organic phase change material, the surfactant and the silane precursor is 10-15:2:10-15.
6. The method for preparing the composite phase change material according to claim 4 or 5, characterized in that: In step S1, the mixing stirring speed is 1000-6000 rpm; the size of the obtained oil droplets is 1-5 μm; And / or, the surfactant includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyl betaine sulfate, polyoxyethylene sorbitan monolaurate, hexadecyl trimethyl ammonium bromide, and dodecyl betaine.
7. The method for preparing a composite phase change material according to claim 4 or 5, characterized in that: In step S2, the temperature of the in-situ polymerization reaction is 60-80°C, and the reaction time is 6-24h; And / or, the in-situ polymerization reaction is carried out under stirring at 500-1000 rpm; and / or, adjusting the pH to 4.5-6.5; And / or, the silane precursor includes at least one of tetraethyl orthosilicate, tetramethylsilane, tetrapropylsilane, triethoxysilane, trimethoxysilane, disubstituted silane Si(OR)2X2 or monosubstituted silane Si(OR)3X.
8. The method for preparing a composite phase change material according to claim 4 or 5, characterized in that: In step S3, the reaction temperature is -70°C to 0°C; And / or, the amount of the alkyl lithium is 1-3% of the mass of the microcapsule; And / or, the reaction is carried out under a protective atmosphere; And / or, the alkyl lithium includes at least one of methyl lithium, ethyl lithium and n-butyl lithium; And / or, the aprotic solvent includes at least one of tetrahydrofuran, dimethoxyethane, diethyl ether, acetonitrile, propionitrile and dimethyl sulfoxide.
9. A lithium ion battery, characterized in that: A composite phase change material comprising the composite phase change material according to any one of claims 1 to 3 or a composite phase change material prepared by the preparation method according to any one of claims 4 to 8; Optionally, the composite phase change material is added to the electrolyte of a lithium-ion battery; Further optionally, the addition amount of the composite phase change material satisfies: M add =T max ·M battery ·C battery / L / ω, where T max The maximum temperature rise allowed by the battery, in degrees Celsius, C battery The specific heat capacity of the battery, in J / g·℃, M battery is the mass of the battery in g, L is the latent heat of the phase change material in J / g, and ω is the mass fraction of the organic phase change material in the composite phase change material.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.
